Analisis Persebaran Kegiatan Ekonomi Unit Usaha Mikro Kecil dan Menengah (UMKM) Kelurahan Sukapada - Hanifa Sukma; Neza Lu’lu Humaira Putri Irawan; Reisha Herliawati; Wulan Tasnita (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
This research was conducted to analyze the distribution factors of UMKM in the Sukapada Subdistrict area, Bandung City. One of the author's considerations was to make UMKM in the Supada Subdistrict area the object of research because they have diverse geographical conditions. This research uses descriptive and spatial methods. Data was collected through field surveys using the Avenza Maps application and interviews with 5 UMKM actors. The research results show that the distribution of UMKM in Sukapada Subdistrict is uneven. Factors that influence the distribution of UMKM in Sukapada Subdistrict include geographic concepts such as location, distance, affordability and morphology. UMKM that are located in strategic locations, close to city centers or markets, have easier access to consumers and suppliers, so they have a higher chance of success. Internal and external factors within entrepreneurs such as business capital, skills, access to information, government policies, infrastructure and competition also influence the distribution of UMKM. The results of this research can help the government in formulating appropriate policies to support the development of UMKM in Sukapada Village.